Uji efek analgetik infusa daun sukun (artocarpus altilis forst) terhadap mencit putih ( mus musculus l) jantan diinduksi asam asetata 1% - nisa aulia; novia sinata (Jurnal Penelitian Farmasi Indonesia, 2019)
ABSTRACTA study of the analgesic effect of breadfruit leaf infusion (ArtocarpusaltilisForst) on male white mice (Musmusculus L) was induced by 1% acetic acid. This study aims to look at the effect of the analgesic effect of breadfruit leaf infusion (ArtocarpusaltilisForst) on male white mice (Musmusculus L) by using the Writhing Test method. Experimental animals were divided into 5 groups. The negative control group was only given aquadest, the positive group was given acetylsalicylic acid at a dose of 1.3 mg / 20 gBB suspended with 1% Na CMC, the treatment group was given breadfruit leaf infusion preparation (ArtocarpusaltilisForst) with a concentration of 5%, 10% and 20 %. The experimental animals were given an oral preparation of 1% BB, 30 minutes after which each group was induced with 1% acetic acid as much as 0.1 ml. The data obtained is processed using two-way Analysis of Variance (ANOVA). The results showed that breadfruit leaf infusion (ArtocarpusaltilisForst) had an analgesic effect similar to acetylsalicylic acid (positive control) at 10% and 20% concentrations, significantly different from negative controland 5% infusion concentration (p <0.05).